Analisis Kebutuhan Pengembangan E-Modul Berbasis Discovery Learning - Falah, Mutia Al; Sari, Silvi Yulia; Ridal, Letmi Dwi; Dewi, Wahyuni Satria (TSAQOFAH, 2023)
The development of e-modules based on discovery learning is needed to achieve the demands of education in era 4.0. The purpose of this study is to conduct a needs analysis on the development of e-modules with a discovery learning base for renewable energy material. This research is included in the type of survey research through the use of quantitative research methods. The population in this study were all class X students of SMAN 9 Padang through a research sample of 27 students. The research was conducted in February 2023. Techniques in collecting data through the use of questionnaires designed with a modified Likert scale of 4 answer options, namely strongly agree, agree, disagree, and strongly disagree. From the results of this student analysis, it can be concluded that students need e-module development based on discovery learning for renewable energy material.